Firm Heterogeneity and Wages Under Different Bargaining Regimes: Does a Centralised Union Care for Low-productivity Firms? - Nicole Gürtzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper studies the relationship between wages and the degree of firm heterogeneity in a given industry under different wage setting structures. To derive testable hypotheses, we set up a theoretical model that analyses the sensitivity of wages to the variability in productivity conditions in a unionsised oligopoly framework. The model distinguishes centralised and decentralised wage determination. The theoretical results predict wages to be negatively associated with the degree of firm heterogeneity under centralised wage-setting, as unions internalise negative externalities of a wage increase for low-productivity firms. We test this prediction using a linked employeremployee panel data set from the German mining and manufacturing sector. Consistent with our hypotheses, the empirical results suggest that under industry-level bargaining workers in more heterogeneous sectors receive lower wages than workers in more homogeneous sectors. In contrast, the degree of firm heterogeneity is found to have no negative impact on wages in uncovered firms and under firm-level contracts.
Keywords: J51; J31; C23; L13; 330; Wage-Setting Structure; Unions; Oligopoly; Linked Employer-Employee Data; Lohnbildung; Tarifpolitik; Lohnpolitik; Gewerkschaftlicher Organisationsgrad; Branche; Produktivität; Branche; Deutschland